2003
DOI: 10.4049/jimmunol.171.10.5514
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Human C5a Receptor Antagonist Protects against Disease Pathology in a Rat Model of Inflammatory Bowel Disease

Abstract: The complement system is implicated in the pathogenesis of human inflammatory bowel disease, but the specific role of C5a has never been examined. We have compared the efficacy of an orally active human C5a receptor antagonist (AcPhe[Orn-Pro-d-cyclohexylalanine-Trp-Arg]), prednisolone, and infliximab against trinitrobenzene sulfonic acid (TNBS)-induced colitis in rats. The drugs were administered either 2 days before or 24 h after TNBS instillation, and rats were then examined after 8 days. Drug-free colitis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 49 publications
4
94
1
4
Order By: Relevance
“…This is in pace with reductions observed in other studies. For example, in an animal model of colitis, the treatment with a dose of infliximab, which is similar to the one used in our study, promoted a 45% decrease in local (colonic) levels of TNF-a and a 50% reduction in blood levels of the cytokine (Woodruff et al 2003). Furthermore, infliximab treatment effectively inhibited the expression of the proinflammatory cytokines, IL-6, and IL-1b, while the antiinflammatory cytokine IL-10 was not affected by the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is in pace with reductions observed in other studies. For example, in an animal model of colitis, the treatment with a dose of infliximab, which is similar to the one used in our study, promoted a 45% decrease in local (colonic) levels of TNF-a and a 50% reduction in blood levels of the cytokine (Woodruff et al 2003). Furthermore, infliximab treatment effectively inhibited the expression of the proinflammatory cytokines, IL-6, and IL-1b, while the antiinflammatory cytokine IL-10 was not affected by the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Examples are that C5a anaphylatoxin can induce the release of TNF-␣, IL-6, and IL-1 from inflamed colonic tissue (44 -46) and the generation of IL-8, IL-6, TNF-␣, IL-10, and IL-1 from retinal pigment epithelial cells (47). Moreover, recent studies have shown that C5a receptor antagonists protect against disease in a rat model of IBD (48).…”
Section: Discussionmentioning
confidence: 99%
“…Every time rhabdomyolysis was induced, a similar number of sham (glycerol)-injected rats that had been subjected to the same procedures before and after injection was used to serve as control groups. After glycerol injection, rats were immediately treated with saline (sham treatment) or with a single dose of infliximab (5 mg/kg ip, Centocor BV, Leiden, Holland) (40). In a separate series of experiments, using the same model, rats were treated with a single intraperitoneal dose of the RIP1 inhibitor necrostatin-1 (1.65 mg/kg, Sigma-Aldrich, St. Louis, MO) (16) or infliximab (5 mg/kg, Centocor BV), or their combination at the same doses used alone.…”
Section: Methodsmentioning
confidence: 99%